Adult growth hormone deficiency: current understanding, diagnosis and treatment - Yuen, Kevin C.J. (Henry Stewart Talks, 2023)
Adult GHD diagnosis, Adult GHD treatment, Screening of adult GHD, AACE 2019 CPG algorithm, Pros and cons of GH stimulation tests, Starting doses recommendations in GHD adults, Use of GH for anti-aging, Long-term effects of GH, High prevalence of undiagnosed GHD in transition patients, Use of GH for fertility and during pregnancy, Use of GH for sports, LAGH preparations